P-482 Male Fertility preservation and pregnancy outcomes in patients facing gonadotoxic therapies. (30th June 2022) - Balakumar, V; Sirisena, A; Milne, P; Ramalingam, M; Kini, S
Abstract: Study question: Emergency Fertility preservation in male patients- utilisation rate of the stored sperms and pregnancy outcomes Summary answer: 99% of men were able to cryopreserve their sperm before gonadotoxic therapy.9% of the sample were used and of them 62% had successful live birth. What is known already: The testis is highly susceptible to the toxic effects of radiation and chemotherapy at all stages of life. Cytotoxic chemotherapy and radiotherapy may produce long-lasting or persistent damage to primordial sperm cells, leading to oligo- or azoospermia. Clinicians should inform patients receiving potentially gonadotoxic therapies about options for fertility preservation and future reproduction prior to the initiation of such treatment. The most common strategy to preserve fertility is cryopreservation of sperm before treatment for later use. Cryopreservation of testicular tissue from prepubescent males remains experimental. Study design, size, duration: A retrospective analysis was performed in 367 patients who underwent emergency fertility preservation in our tertiary centre, during a period of 30 years between January 1991 to December 2021. Participants/materials, setting, methods: An Infertility database for embryology and andrology s (IDEAS) was used for the data collection and analysis. Patient's age, reasons for fertility preservation, type of cancer and benign conditions, sperm characteristics, whether the samples were utilized for fertility treatment and any treatment outcomes were included in the analysis. Main results and the role of chance: The median age for the men who presented for fertility preservation is 30 years (Range 15- 55). The median number of straws is 9 (Range 1– 18). The referral was made from oncology (33%), haematology (28%) Urology (19%) and other departments (20%). The majority had a diagnosis was testicular cancer (50%), lymphoma (20%), leukaemia (5%) and other causes (25%). A total of 99 % of men had sperms frozen from the ejaculated semen and 1% underwent surgical sperm retrieval for cryopreservation. More than half the population of men at the time of cryopreservation were normospermic in 59%, the rest had oligo/asthenospermia in 40 % and azoospermia in 1 %. Cryopreservation was not possible in 1 % of the patients as they were unable to produce a sample. Nine percent of the sample were used for treatment and of them 62 % resulted in successful Livebirths. Intracytoplasmic sperm injection was the main treatment of choice. The mean Straws were perished electively in 2% and following death in 0.5 % of the study population. Limitations, reasons for caution: Concerns about the welfare of resulting offspring, whether due to an expected shortened lifespan of the parent or effects of cancer or infertility treatment (in the present state of knowledge) ordinarily are not a sufficient reason to deny cancer patients assistance in reproducing. Wider implications of the findings: The rate of use of cryopreserved sperm in cancer patients is low.Cancer patients were more likely than non-cancer patients to use or continue storage of banked samples. Sperm banks should be aware of the low rates of straw use and destruction by patients. Trial registration number: not applicable